Gendered Feed Assessment Tool (G-FEAST) individual farmer interview questionnaire - Lukuyu, Ben A.; Eerdewijk, Anouka van; Kinati, Wole; Sultana, N.; Mulema, Annet A.; Duncan, Alan J. (International Livestock Research Institute, 2019)
You can download 'Gendered Feed Assessment Tool (G-FEAST) group discussion guide' from: https://hdl.handle.net/10568/100243